From the history of Polish adult education theory and practice in the Third Republic of Poland. The Academic Andragogy Society (1993‒2023) - Maliszewski, Tomasz (Rocznik andragogiczny, 2024)
The year 2023 marks the 30th anniversary of the establishment of the Academic Andragogy Society (in Polish: Akademickie Towarzystwo Andragogiczne, ATA), a nationwide social research organization based in Polan reflects on its origins, history, organizational transformations, and the most important trends in its activity over the past three decades. The author also tries to assess the achievements of the Academic Andragogy Society in the key areas of its activity specified upon its establishment. The article is an interesting contribution to the history and practice of Polish adult education and the social research movement in social sciences in the Third Republic of Poland.